On the Chernikova theorem on well-factorizable groups - Dovzhenko, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We describe finite groups G every subgroup of which that does not belong to the Frattini subgroup ϕ (G) has a complement.